Pengaruh Harga dan Word of Mouth terhadap Keputusan Pembelian pada Pokdakan Barokah Sentra Budidaya Ikan Terintegrasi Desa Sungai Gerong - Nanda Mareta; Efan Elpanso (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2024)
This study aims to find out and analyze the influence of Price (X1) and Word of Mouth (X2) on Purchase Decisions (Y) in the Pokdakan Barokah Integrated Fish Farming Center located in Sungai Gerong Village. The observed phenomenon shows that consumers' purchasing decisions for fish farming products are not only influenced by competitive price factors, but also by the power of word-of-mouth promotion or word of mouth that develops in the surrounding community. The research method used is a quantitative approach with an associative design. Data collection was carried out through the distribution of questionnaires to 100 respondents determined by the quota sampling technique. Data analysis was carried out through several stages, namely the validity and reliability test of the instrument, the classical assumption test (normality, multicollinearity, and heteroscedasticity), multiple linear regression analysis, the determination coefficient test (R²), and the hypothesis test through the t-test and the F test. The results of the data analysis showed that the Price variable had a positive and significant effect on the Purchase Decision with a significance value of 0.000 and a tcal value of 6.686 which was greater than table of 1,660. Likewise, the Word of Mouth variable has a positive and significant effect on the Purchase Decision with a significance value of 0.000 and a calculation of 9.688 > a table of 1.660. In addition, simultaneously the two independent variables (Price and Word of Mouth) had a significant effect on the Purchase Decision with a Fcal value of 111,480 > Ftable 3.94 and a significance of 0.000. The conclusion of this study is that both partially and simultaneously, the variables Price and Word of Mouth have a significant influence on Purchase Decisions in Pokdakan Barokah.